1998
DOI: 10.1111/j.1524-4725.1998.tb04211.x
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Metastases Mimicking Alopecia Areata

Abstract: This represents the first case in which PSTT presented initially with metastases, and specifically, with cutaneous metastases. A new primary tumor source of alopecia neoplastica is presented. The role of mitotic counts in predicting prognosis in PSTT is supported. Alopecia areata was mimicked very closely. Dermatologists should be alert to any features atypical of alopecia areata, including erythema, induration, or palpability, and maintain a low threshold for biopsy in atypical cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Secondary alopecia neoplastica almost exclusively occurs in females with metastatic breast cancer being the most common etiology by far . Others causes of secondary alopecia neoplastica are more rare and include metastatic malignancies of pulmonary, gastrointestinal or reproductive system origins . A history of previous malignancy and/or the concomitant existence of distant metastases elsewhere may alert the provider to the neoplastic origin of alopecia in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary alopecia neoplastica almost exclusively occurs in females with metastatic breast cancer being the most common etiology by far . Others causes of secondary alopecia neoplastica are more rare and include metastatic malignancies of pulmonary, gastrointestinal or reproductive system origins . A history of previous malignancy and/or the concomitant existence of distant metastases elsewhere may alert the provider to the neoplastic origin of alopecia in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…3 reported a case of alopecia neoplastica due to metastasis from gastric carcinoma, and Yuen et al . 4 reported a case in which the primary tumour was a placental trophoblastic tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Alopecia neoplastica is usually a presentation of metastasis from breast cancer, and any other primary site is extremely rare. Kohno et al 3 reported a case of alopecia neoplastica due to metastasis from gastric carcinoma, and Yuen et al 4 reported a case in which the primary tumour was a placental trophoblastic tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,23 Similar to the widely disseminated metastases that can be seen in choriocarcinoma, PSTT can also spread to the vagina, ovary, liver, bowel, kidneys, pancreas, brain, skin, and pelvic and para-aortic lymph nodes. 15,[24][25][26][27] Serum levels of β-hCG are typically in the thousands of IU/L, which is much lower than that of choriocarcinoma. 23 Given both its rarity and wide variation of presentation, it is easy to understand why PSTT may be incorrectly diagnosed in nearly a third of patients.…”
Section: Clinical Presentationmentioning
confidence: 99%